Penerapan Hypertext Transfer Protocol Web Server untuk Over-The-Air Auto Update Firmware pada Perangkat IoT - Yusri, Iin Karmila; Kasim, Kasim; Akbar, Andi Muhammad (Elektron : Jurnal Ilmiah, 2022)
Devices in the IoT system are located in many places and difficult to be accesses physically by system administrator. Besides, short life cycle of software/firmware requires to be updated periodically in order to improve the embedded system function to meet the system requirements. These conditions shows the difficulty to update the devices physically. Auto update firmware over the air system became a solution for physical acsess and periodically updated problem which developed by implementing Hypertext Transfer Protocol Web Server. This research is part of study of developing IoT Management System in agricultural environment. This system is in form of web application as an interface to control and manage the update system and a software for update firmware that embedded in the IoT devices. The results shows that the system is able to update firmware of the IoT devices that connected to different network at the same time automatically. Besides, this system can serve around 29,000 request for firmware update concurrently.